Peningkatan Daya Saing Produk UMKM melalui Pelatihan Pengemasan pada Rantie Bakery Palembang - Andriyani, Titi; Suharmanto, Ardelia; Rizkiyanti, Shally; Munthe, LydiaRoma Junita; Rafansyah, M. Aidil; Nurhalimah, Alya (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aimed to support Rantie Bakery, a microenterprise in Palembang, in strengthening its competitiveness through packaging innovation. Previously, the business relied on simple packaging that neither conveyed brand identity nor provided essential product information, limiting its market value. Using a Participatory Action Research (PAR) approach, the program involved preparation, training, mentoring, evaluation, and follow-up. Through Canva-based training, the bakery owner gained new knowledge and skills, recognizing packaging as both a visual communication tool and a branding strategy. The outcomes show enhanced capacity in designing packaging aligned with the Visibility, Information, Emotional Appeal, Workability (VIEW) framework. The new packaging is visually appealing, informative, functional, and eco-friendly. This initiative is expected to improve brand image, boost sales, and better position Rantie Bakery to compete in local and digital markets.